Allowance for Corporate Equity: The Latest Developments in European Union Law - Klemenčić, Irena; Pribisalić, Luka (LeXonomica, 2022)
There are two ways of financing companies, namely equity financing and debt financing. These two ways of financing companies are relevant for tax law because the payment of interest arising from loan financing reduces the tax base of income tax, and the payment of dividends paid due to ownership of the company does not reduce the tax liability of the company. Therefore, over time, attempting to achieve neutrality in corporate financing was a challenging task. One of those ways is Allowance for Corporate Equity. In May 2022, the European Commission adopted a Proposal for a Council Directive on laying down rules on a debt-equity bias reduction allowance and on limiting the deductibility of interest for corporate income tax purposes, the so-called DEBRA proposal, which seeks to reduce the tax base of corporate income tax arising from equity financing. Consequently, this paper will briefly discuss the Allowance for Corporate Equity, give an overview of the Proposal for a Council Directive on laying down rules on a debt-equity bias reduction allowance and on limiting the deductibility of interest for corporate income tax purposes and assess the European Commission proposal.Povzetek. Obstajata dva načina financiranja podjetij, in sicer lastniško in dolžniško financiranje. Ta dva načina financiranja podjetij sta pomembna za davčno zakonodajo, saj plačilo obresti, ki izhajajo iz posojilnega financiranja, zmanjšuje davčno osnovo za dohodnino, plačilo dividend, izplačanih zaradi lastništva podjetja, pa ne zmanjšuje davčne obveznosti podjetja. Zato je bil poskus doseganja nevtralnosti pri financiranju podjetij zahtevna naloga. Eden od teh načinov je olajšava za lastniški kapital podjetij. Evropska komisija je maja 2022 sprejela predlog direktive Sveta o določitvi pravil o olajšavi za zmanjšanje naklonjenosti zadolževanju v razmerju do lastniškega kapitala in o omejitvi odbitka obresti za namene davka od dohodkov pravnih oseb, t. i. predlog DEBRA, katerega namen je zmanjšati davčno osnovo davka od dohodkov pravnih oseb, ki izhaja iz lastniškega financiranja. Zato bo v tem prispevku na kratko obravnavana olajšava za lastniški kapital podjetij, podan pregled predloga direktive Sveta o določitvi pravil o olajšavi za zmanjšanje naklonjenosti zadolževanju v razmerju do lastniškega kapitala in o omejitvi odbitka obresti za namene davka od dohodkov pravnih oseb in ocenjen predlog Evropske komisije.